Rapid identification of seismic damage in tall buildings by using acceleration response time histories : effects of modelling errors & correction measures - Liyanarachchi, Navindra; Pennung Warnitchai; Punchet Thammarak; Anwar, Naveed; Computer and Structures Inc. (CSI), USA; Asian Institute of Technology Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2021)
This study presents a novel technique to identify the seismic damage to a Tall building by using accelerometers on a limited number of floors. The procedure was based on modal decomposition considering the concept of mode of vibration where any complex response of the structure could be defined as a summation of modal responses. The modal decomposition was carried out by a new technique called the 2Orthogonal Filter3 approach, where the orthogonality of the modes was taken into consideration to obtain the responses. The acceleration records from the accelerometers during a seismic event were passed through the Orthogonal Filter Matrix to get the modal accelerations directly. These modal accelerations were multiplied by the mode shape of the structure and summed to obtain the acceleration of any floor. In the real-world scenario, the dynamic properties such as natural frequencies and mode shapes of the real structure differ from the numerical model of the structure due to many complexities. Hence, a model updating procedure was performed to match the dynamic properties of the real building with that of the numerical model. Modal accelerations were double integrated to find the model coordinates, which were then used to calculate the displacement and inter-story drifts. The modal coordinates were converted to modal forces based on the hysteresis behaviour identified for each mode by conducting a modal cyclic pushover analysis. These modal forces could then obtain any force related response. The seismic damage to the structure could be identified by comparing these seismic demands with the capacity of the structure. The proposed technique was verified by conducting a Non-Linear Response History Analysis (NLRHA) Procedure. It was also compared with the conventional FEM updating procedure for damage identification and shown that it predicted the responses better than the traditional approach since the actual acceleration of the building during the seismic event was considered.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Structural Engineering, School of Engineering and Technology
Thesis (M. Eng.) - Asian Institute of Technology, 2021
Keywords: Buildings -- Earthquake effects; Acceleration (Mechanics)